Effects of habitat and substrate complexity on shallow sublittoral fish assemblages in the Cyclades Archipelago, North-eastern Mediterranean Sea - GIAKOUMI, S.; KOKKORIS, G.D. (Mediterranean Marine Science, 2013)
This is the first study to explore fish community structure and its relations to habitat and topographic complexity in the shallow coastal waters of the Cyclades Archipelago, North-eastern Mediterranean Sea. In situ visual surveys were carried out at 233 sampling sites in 26 islands of the Cyclades Archipelago. Fish community parameters and biomass were estimated across seven substrate types: sand, seagrass, vertical walls, boulders, horizontal/subhorizontal continuous rock, rocky substrate with patches of sand, and rocky substrate with patches of sand and Posidonia oceanica. Topographic complexity and percentage of algal cover were estimated on hard substrate. Substrate type was found to be a determining factor affecting the structure and composition of fish assemblages. Species number, abundance and biomass were significantly lower in sandy areas and always higher on hard substrates, with seagrass habitats presenting intermediate values. Topographic complexity in rocky bottoms did not seem to affect species richness, density or biomass. This study provides a baseline for future evaluation of changes produced by potential management actions such as the creation of marine protected areas in the study region.